Аналіз інструментів та платформ для впроваджень ефективних стратегій просування інтернет-магазину - Луданов, Ігор; Вовк, Наталія (Видавництво Львівської політехніки, 2025)
This work analyzes various tools and platforms for promoting online stores using efficient, low-budget strategies. The research focuses on the functionality and potential of services such as Facebook, OLX.ua, Prom.ua, and Google Ads. It explores the benefits of combining free and paid advertising methods to reach target audiences effectively. Additionally, it highlights the importance of branding, audience analysis, and using business management systems like Salesdrive to build customer bases and enhance sales.
Keywords: інтернет-магазин; маркетинг; реклама; Facebook; OLX; Prom.ua; Google Ads; стратегія просування; цільова аудиторія; бізнес-інструменти